ANALISIS AKAR KONFLIK SAMPIT MELALUI TEORI DEPRIVASI - Alexandra, Frisca (Global and Policy Journal of International Relations, 2018)
One of the most vulnerable issues to be the trigger for conflict is the issue of identity. The sense of identity can quickly turn into a response to threats. The response to these threats will often end up in conflict. Ethnicity is one of the dimension of identity. Ethnic conflicts often show that ethnicity is the cause of the outbreak of conflict but the root causes of ethnic conflict can not be seen from a single factor because ethnic conflict is a fairly complex conflict. Sampit conflict is one of the conflicts involving ethnicity occurring in Indonesia but this conflict certainly can not be viewed solely as a conflict between ethnic Dayaks and Madurese, using the approach of Theory of Deprivation by Robert Ted Gurr, the various allegations of the outbreak of ethnic conflict in Sampit actually led at one conclusion that there has been a deprivation within society that causes the community to feel frustrated and ultimately to act aggression. To find out and analyze the deprivation condition that occurred in Sampit first we must know and understand about the situation and conditions in Sampit before the conflict broke out in 2001. The exposure will be focused on the social, political, economic and cultural conditions of the people of Central Kalimantan, especially between the two conflicting ethnic groups that are ethnic Dayaks and Madurese. Keywords: Root Conflict, Deprivation, Sampit ConflictDOI : https://doi.org/10.33005/jgp.v6i02.1821